Ultrasound guided fine needle aspiration cytology of space occupying lesions of liver - Rastogi, Naincy; Bhake, Arvind; Agarwal, Deepika; Wankhede, Akanksha (International Journal of Research in Medical Sciences, 2018)
Background: The liver is a common site for primary and secondary tumors; most often from malignant tumors within the abdomen and from extra-abdominal primary malignant neoplasm, but also for sarcomas and lymphomas. The main indication of fine-needle aspiration cytology (FNAC) of the liver is diagnosis of single or multiple space occupying lesions. This study aims to evaluate the cyto-morphology of primary and secondary neoplasms of liver and non-neoplastic conditions in the smears of ultrasound guided fine needle aspiration of SOL of liver, to evaluate the cytomorphologic features and to evaluate the erroneous diagnosis when compared with cell block preparation of aspirate (tissue diagnosis). Methods: This study is hospital-based prospective study including 57 patients with space occupying lesion of the liver mass. FNAC were carried out under the guidance of sonography and/or computed tomography. The staining performed were conventional for smears of the aspirate. The cell blocks were prepared from the aspirates by the established procedures. The values of correlation were bought out. Results: Males predominated over females. The distribution of cases for cyto-diagnosis were as follows; cirrhosis with hepatic granulosa (3 cases),pyogenic abscess (3 cases), hepatic adenoma (2 cases), Focal nodular hyperplasia (2 cases), hepatoblastoma (1 case), hepatocellular carcinoma (17 cases), adenocarcinoma deposits (20 cases), deposits of small cell carcinoma (3 cases), deposits of ductal carcinoma (2 cases) and 1 case each of deposits of squamous cell carcinoma, non-Hodgkin’s lymphoma, neuroendocrine tumor and adeno-squamous carcinoma. Values of correlation were as follows: sensitivity 97.61%, specificity 100%, PPV 100%, NPV 97.82% and diagnostic accuracy of 98.85%. Conclusions: FNAC is concluded to be first rank diagnostic procedure in diagnosis of SOL of liver of varied etiology with high values of NPV and PPV. It is also concluded that it helps in staging of metastatic malignancies.